The influence of the supply chain agents on the new product development's performance: an analysis based on the multi-group moderation - Carvalho, Luciano Castro de (2014)
This study aimed to verify the influence of the supply chain agents on the new product development’s performance when those agents are analyzed jointly. The motivation for this goal rose up from some studies that claimed for the consideration of the supply chain integration as a multi-dimensional construct, encompassing manufacturing, supplier and customer involvement into NPD; and due to the lack of information about the individual influences of those agents on new product development’s performance. Under these considerations, we built an analytical model based on Social Capital and Absorptive Capacity Theory, raising hypotheses from the literature review and connecting constructs as cooperation, supplier involvement into NPD, customer involvement into NPD, manufacturing involvement into NPD, anticipation of new technologies, continuous improvement, NPD’s operational performance, NPD’s marketing performance and NPD’s business performance. To test the hypotheses we also considered three moderating variables, as environmental turbulence (low, medium and high levels), industry (electronics, machinery and transport equipment) and location (American, European and Asian countries). To run the model, we used the data from High Performance Manufacturing (HPM)’s project that covers 339 companies from electronics, machinery and transport equipment industries placed in eleven countries. We tested the hypotheses through confirmatory factor analysis (CFA) including multi-group moderation for the three moderating variables mentioned previously. The main results pointed out that the hypotheses regard to cooperation were confirmed in environments with medium level of turbulence while the hypotheses related to NPD performance was not rejected in electronics and machinery industry, in low levels of environmental turbulence and in Asian countries. Moreover, we found out that, under the same conditions, suppliers, customers and manufacturing influence differently on new product development performance. Thus, supplier involvement influences directly the operational performance and influences indirectly the marketing and business performance in low levels of environmental turbulence, in transport equipment industry and in American and European countries. Likewise, customer involvement influenced directly the operational performance and indirectly the marketing and business performance in medium and high levels of environmental turbulence, in the machinery industry and in Asian countries. Suppliers and customers don’t influence directly the marketing and business performance and don’t influence indirectly the operational performance. Surprisingly, manufacturing involvement didn’t influence any kind of new product development’s performance in all scenarios presented.